Nonlinear constrained optimizer and parallel processing for golden block line search - Nguyen, Due T.; Tang, Wilson H.; Tung, Yeou K.; Runesha, Hakizumwami B. (Computer Assisted Methods in Engineering and Science, 2023)
Generalized exponential penalty functions are constructed for the multiplier methods in solving nonlinear programming problems. The non-smooth extreme constraint Gext is replaced by a single smooth constraint Gs by using the generalized exponential function (base a > 1). The well-known K.S. function is found to be a special case of our proposed formulation . Parallel processing for Golden block line search algorithm is then summarized, which can also be integrated into our formulation. Both small and large-scale nonlinear programming problems (up to 2000 variables and 2000 nonlinear constraints) have been solved to validate the proposed algorithms.